Hubungan Antara Karakteristik Internal dan Eksternal Peternak Sapi Potong dan Adopsi Inovasi Inseminasi Buatan - Aida Vitayala S Hubeis; Amiruddin Saleh; Budi Saharjo; Mursyid Ma’sum (Jurnal Penyuluhan, 2013)
The objective of the research is to describe and analyze implementation and rate of adopted artificial insemination (AI) innovation on slaughter cattle’s farmers. Specifically, the objectives are to describe (1) the characteristics of internal and external of slaughter cattle’s farmers, (2) the implementation and the rate of AI’s adoption, and (3) the relationship of internal and external characteristics of slaughter cattle’s farmers and adoption of AI. The research is conducted at Kecamatan Geger Kabupaten Bangkalan and Kecamatan Mantup Kabupaten Lamongan in East Java Province and at Kecamatan Penebel Kabupaten Tabanan in Bali Province. This research is designed as a correlational descreptive survey. The number of sample is 240 respondents and using stratified random sampling method. Data collection is completed using questionnaires, interview and field observation. Structural equation modeling is applied to analyze the relationship and the influence pattern among variables. The average of AI implementation aspects by the farmers is 51.1% and the average of the rate of AI adoption is 2.39 years. The internal and external characteristic of slaughter cattle’s farmer simultaneously are directly and positively influence the implementation of AI and the rate of AI adoption.Keywords: cattle breeding policy, perception, artificial insemination